Pengaruh Psikoedukasi dalam Meningkatkan Kemampuan Caregiver terhadap Tingkat Pengetahuan Ibu Muda Pendamping Lansia di Puton Diwek Jombang - Nurmalisyah, Fitri Firanda; Imaningsih, Agustin Nur; Aditya, Arya Rakha; Putri, Yusi Marhaeni Oktaviana; Khoirunnisa, Fathonah Nilam; Agustin, Putri Amelia Verani; Palwa, Adizty Senditha (Universitas Pahlawan Tuanku Tambusai, 2025)
Introduction: This study aimed to determine the effect of psychoeducation on improving caregivers' abilities regarding the knowledge level of young female companions of the elderly in Puton Village, Diwek District, Jombang Regency. Methods: This study employed an analytical pre-experimental research design with a one-group pre-post test design. Results: The research results showed an increase in the average knowledge level of young female companions of the elderly by 28.667 after receiving psychoeducation, from an average of 55.11 before psychoeducation to 83.78 after psychoeducation. Conclusion: There was an effect of psychoeducation on improving caregivers' abilities regarding